Type synthesis of 2R2T parallel mechanisms based on motion equivalent chain method. (December 2014) - Ye, Wei; Fang, Yuefa; Guo, Sheng; Qu, Haibo
In this paper, the motion equivalent chain method is proposed and then applied to the type synthesis of a class of 2R2T parallel mechanism. The equivalent serial chains are synthesized for a specific 2R2T motion pattern based on screw theory. Feasible limb structures that provide a constraint couple and a constraint force are enumerated according to the reciprocity of the twist and wrench systems. Several motion equivalent single loop chains are constructed with the equivalent serial chains. Using motion equivalent single loop chains to replace the equivalent serial chains, a class of 2R2T parallel mechanisms is obtained based on the foundation of motion equivalent single loop chain structures.